Análise biomecânica de próteses implantossuportadas parafusadas e cimentadas por meio do método dos elementos finitos - Guilherme Costa Carvalho Silva (2013)
The implant-supported prostheses can be retained by screw or by cement. An important factor that may influence the choice of one of two types of retention is the distinct biomechanical behavior between them. Using the 3D finite element method, the stresses and displacement on the screws, implants, abutments, and periimplantar bone were compared. Two distinct models were constructed: porcelain fused to metal partial fixed implant supported prosthesis of three elements, retained by screws (SFP) or cement (CFP). Initially, the retaining screws of the prostheses were torqued to obtain the value of the preload. Then, vertical (100 N) and oblique loads (100 N) were applied to the models on the occlusal surface of the crowns. The maximum von Mises equivalent stresses (SEQV) were obtained on screws, implants, and abutments, while the bone was analyzed by the principal stresses 1 and 3. Displacement among implant, abutment, and screw, and between bone and implant was identified by plotting penetration and gap. The results showed a similar pattern in the stresses distribution between the two types of prostheses in all simulations. However, the peaks of SEQV were higher in the SFP. The maximum stress was 24% higher in the screw of the SFP compared to the CFP under oblique loading. In the implants, the maximum SEQV were 49% and 22% higher in the SFP under vertical and oblique loads, respectively. In the abutments, the maximum SEQV were 51% and 13% higher in the SFP under vertical and oblique loads, respectively. In the analysis of the prosthetic screw under vertical load, which evaluated the effect of loading over the pre-tensioned screw, there was a higher decrease in stress and preload in the SFP: stress decreased by 23% against 6% in CFP, and preload was reduced by 31% in the SFP against 19% in the CFP. In the study of the displacement under vertical load, the SFP showed a greater penetration concentrated in the threads of the screw, while the CFP showed penetration located between abutment and implant. The gap was greater (118%) in the SFP, and concentrated on the abutment extension. Under oblique load, the displacement pattern was similar for both prostheses, but with values 66% and 96% higher for penetration and gap, respectively, for the SFP. Under the criterion of principal stresses, the SFP showed similar values in the periimplant bone compared with the CFP, when considering the 1. The analysis of the 3 showed stress peaks 28% higher in the SFP, considering vertical and oblique loads. The displacement in bone showed a similar pattern between the prostheses for both penetration and gap, under vertical and oblique loads, with also similar values. It was concluded that the SFP showed a higher biomechanical risk of failure in the screw, implants, abutments, and in bone structure under 3 stresses, compared to the CFP.